The influence of halo assembly on galaxies and galaxy groups - Zapata, Tatiana (2009)
In this paper, we study the variations of group galaxy properties according to the assembly history in SDSS-DR6 selected groups. Using mock SDSS group catalogues, we find two suitable indicators of group formation time: i) the isolation of the group, defined as the distance to the nearest neighbor in terms of its virial radius, and ii) the concentration, measured as the group inner density calculated using the fifth nearest bright galaxy to the group centre. Groups within narrow ranges of mass in the mock catalogue show increasing group age with isolation and concentration. However, in the observational data the stellar age, as indicated by the spectral type, only shows a correlation with concentration. We study groups of similar mass and different assembly history, finding important differences in their galaxy population. Particularly, in high mass SDSS groups, the number of members, mass-to-light ratios, red galaxy fractions and the magnitude difference between the brightest and second brightest group galaxies, show different trends as a function of isolation and concentration, even when it is expected that the latter two quantities correlate with group age. Conversely, low mass SDSS groups appear to be less sensitive to their assembly history. The correlations detected in the SDSS are not consistent with the trends measured in the mock catalogues. However, discrepancies can be explained in terms of the disagreement found in the age-isolation trends, suggesting that the model might be overestimating the effects of environment.We discuss how the modeling of the cold gas in satellite galaxies could be responsible for this problem. These results can be used to improve our understanding of the evolution of galaxies in high-density environments.